EFFECT OF APPLICATION GIBBERELLIN AND SOAKING TIME ON THE GERMINATION OF TOBACCO SEEDS (Nicotiana tabacum L.) - Lu'lu' Kholidah Fauziah; Nindy Permatasari; Resti Puspa Kartika Sari; Maisuri Hardani; Sismita Sari; Maryanti Maryanti; Devita Harijayanti (Universitas Veteran Bangun Nusantara, 2026)
Tobacco (Nicotiana tabacum L.) is a plantation commodity that plays a strategic role in supporting the agricultural sector. One of the problems in tobacco cultivation is the low germination percentage of seed because of seed dormancy. This study aims to determine the effects of gibberellin concentration and soaking duration on the germination percentage and germination index of tobacco seeds. This study was conducted from February to March 2026 at the Laboratorium Tanaman II, Panen dan Pasca Panen Perkebunan, Politeknik Negeri Lampung. This study used a Completely Randomized Design (CRD) with two factors: Gibberellin concentration (0, 10, 15, and 20 ppm) and soaking duration (1, 3, and 5 hours), with three replications for each treatment. The parameters evaluated were germination percentage and germination index. Data analysis using SPSS was followed by DMRT post-hoc test at 5% significance level. The results showed that gibberellin application and soaking duration had a significant effect on the germination percentage and germination index of tobacco seed. However, no significant interaction was found between the two treatment factors tested. A treatment using gibberellin 20 ppm increased the germination percentage by 5.78% and the germination index by 0.38 compared to the control. Meanwhile, a soaking duration of 5 hours increased the germination percentage by 6.83% and the germination index by 0.40 compared to the control. Keywords: Tobacco, germination percentage, gibberellin, germination index, soaking duration